Identification of managerial competencies of the organizational leaders of the Passifloraceae production sector in the Huila Department - Gil Tovar, Hernando; Lara Figueroa, Derly Cibelly (Cuadernos de Administración, 2020)
Managerial competencies, defined as the “underlying characteristics of an individual that have a causal relationship with effective or superior performance in the job” (Boyatzis, 1982, p. 12), are key to achievement of productive purposes in the Huila department, in Colombia. The present article, as an investigative result, seeks to identify those managerial competencies, both current and required, of the organizational leaders in the Passifloraceae productive sector in the Huila department, in Colombia. The epistemological paradigm used in this article is that of interpretivism. The reasoning method is deductive, and the methodological approach is mixed. The unit of analysis for this study consists of the directors of the associative organizations of Passifloraceae producers in the productive chain, where two types of players are identified: thirteen (13) leaders of organizations producing passion fruit, and five (5) representatives of institutions in the Huila department that influence the sector. The study concludes with the definition of the map of current managerial competences of organizations in the passionfruit productive sector, and is then contrasted with the map of competences required from these. It also highlights the importance of associativity for small producers, the need to continue conducting research in the sector, and the need to intervene through social outreach projects, so as to generate appropriation and training processes for a set of managerial competencies identified herein, which will strengthen management skills and competitiveness in this type of organization, and ensure, over time, generational change within the sector.